Assessing Multiple-Item Manufacturing Capability Measures: A Critical Review - Hensley, Rhonda L.; Utley, Joanne S. (Archives of Business Research, 2018)
This paper critically reviewed empirical studies of manufacturing capabilities to identify possible inconsistencies in the composition and use of multiple item capability measures. In addition, this paper examined the issue of item commonality which is the extent to which questionnaire items corresponding to a capability were used by the studies to measure the capability. This paper also explored the potential effects of inconsistencies in measure composition and use on survey validity and on item commonality. Twenty-seven papers met the review criteria delineated in the paper. Review results revealed a striking lack of consensus in measure sourcing, Likert scale framing and the use of validity checks in measure composition. Furthermore, only six survey items used in the studies can be thought of as high commonality items. Given these results